Usage of personal care product and impact on confidence among male students in Kota Samarahan / Alsee Grace Sitin - Sitin, Alsee Grace; Comry, Mohd Sukri (2017)
Chapter one of this research consists of 10 parts including introduction as the first part of this study. Second part of this study is the background. It will be explaining the background of this study. Third part is problem statement. It stated the problem statement of this study and why the problem should be studied. This part is divided into two section which is theoretical and empirical problem statement. Next part is research questions. This part will list the research questions as the main question to be answer in this study. Fifth part is research objective. It listed down the objective of this research that needs to be achieved at the end of this study. Part six is the hypothesis. It listed down the entire hypothesis regarding to this study. Next part is significant. Under this part, it stated the important and benefits of this study toward readers and future researcher. Part seven will explain the scope of study where it states the target respondent, location and age range. Second last part is definition of terms. This part will be explaining the terms and keyword that always be mention in this study. Last part is conclusion. It will conclude this chapter and link this whole chapter with Chapter Two the Literature Review.